Enhancing Risk Management in an IT Service Company: A COBIT 2019 Framework Approach - Emmanuel Enrique; Melissa Indah Fianty (Kresnamedia Publisher, 2023)
The application of information technology is utilized to support the business activities of companies engaged in IT services. One of the prevailing issues pertains to service delivery delays. This issue is paramount as customer satisfaction ranks among the most pivotal factors for business success, significantly influencing the company's continued prosperity. In response to these challenges, this study assesses the level of IT governance within the company using the 2019 COBIT framework. The methodology employed combines a qualitative approach, integrating data collected through interviews and literature analysis. The study's key performance indicators include APO12 (Managed Risk), BAI10 (Managed Configuration), and DSS04 (Managed Continuity). The findings reveal that the measured capability levels for these objectives are at levels 3, 3, and 2, respectively, falling short of the targeted levels, which are 4, 4, and 3. This indicates a 1-level gap in each process. The recommendations provided concentrate on the management of risk records associated with service delay causes, the proper management of IT resources, and the maintenance of a continuous service system to prevent future delays.